Ethical Dimension of Maqasid al-Shari’ah and its Implication to Human Capital Development - Abdulhameed, Nasir Muhammad (IJISH (International Journal of Islamic Studies and Humanities), 2021)
AbstractThe prescriptions of Shari’ah are aimed at protecting six critical areas of human needs namely; life, religion, mental health, offspring, property, and dignity. Maqasid al-Shari’ah were earlier treated as an aspect of Maslahah Mursalah (public utility). They were treated as separate principles aiding the understanding of the wisdoms and intents of the texts. Transformation in the pattern of life of modern societies caused expansion in the scope of Maqasid. In modern times, Maqasid include aspects of material development that feature in Human Development Index. This paper employed theoretical method and analyzed the ethics embodied in the objectives of Shari’ah. The aim is to find out how the ethics shape human conduct and facilitate non-material aspects of human capital development. Its findings are that, the objectives of Shari’ah on the protection of religion, life, and mind can refine conduct, inspire morality, develop and secure the mind. Thus, the ethics imbued in Shari’ah instructions transform individuals into worthy citizens, shape their life and conduct, and make them productive and sensitive about the well-being of fellow human beings. These changes in human conducts by means of Shari’ah-inspired ethical transformation are a form of non-material aspects of human capital development.